Junior High School Students’ Habits of Mind in Solving Mathematical Problems - Nauli, Novia; Harisman, Yulyanti; Armiati; Yerizon (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2024)
One of mathematical cognitive skills is the problem-solving ability. It is imperative for each student to have a range of abilities in order to deal with or resolve a problem. Habits of mind are abilities that can influence students' ability to solve mathematical problems. It is the aim of this study to examine junior high school students' problem-solving thinking skills. The survey method was used, as opposed to critical observation or qualitative approaches. The sample of this study consisted of 29 ninth graders of junior high school. Data collection was conducted by a test and interviews. According to the findings from the data analysis in this study, students with strong problem-solving abilities exhibited four indicators of thinking habits: persistence, thinking about thinking, thinking flexibility, and the ability to apply past knowledge to new situations. Students with average problem-solving abilities also displayed four indicators of thinking habits, but were lacking in three of them: thinking about thinking, thinking flexibility, and applying past knowledge. Students with poor problem-solving abilities, on the other hand, laked all the indicators of thinking habits.